An Innovative Regulatory Approach to Stimulate Competition in Long-Distance Passenger Rail Transport - Alexander Eisenkopf; Andreas Knorr (Wirtschaftsdienst)
Abstract Regulatory efforts to introduce effective intramodal competition to the rail sector, in particular to the long-distance intercity market segment, have so far achieved only very limited success in most countries. Germany is a case in point. Even 25 years after the fundamental 1994 ‘rail structure reform’, which eliminated the legal network monopoly of the former Deutsche Bundesbahn (DB), the combined market share of all competitors for long-distance passenger services remains stuck at “significantly below one per cent” (Bundesnetzagentur 2018, 22). This figure stands in stark contrast to the competitors’ market shares of some 26% for short-distance (regional) services — where a competition for the market regime has been established — and around 50% of the rail cargo segment — which is governed by an open access regime. In this paper, we make the case for an alternative regulatory regime to substantially increase effective intramodal competition in the intercity rail passenger market. Our proposal addresses, and helps to overcome, the two major entry barriers faced by competitors: the massive investment needs in rolling stock on the one hand and reliable infrastructure access on the other.